Legal Review of the Validity of Electronic Medical Records as Valid Evidence in Medical Disputes - Kharisma Berlian Sjukri; Happy Yulia Anggraeni (LifeSciFi, 2026)
Electronic medical records are a product of digitalization in the healthcare sector and have been recognized under Indonesian law. However, their validity as evidence in medical disputes remains normatively uncertain due to the overlap between health law, information technology law, and the law of evidence. This study aims to examine the legality of electronic medical records as evidence in civil and criminal proceedings, as well as to identify the validity criteria and evidentiary strength of electronic medical records in medical disputes. This research employs a normative juridical method using a literature study approach, analyzing legislation, court decisions, and scholarly works through systematic and comparative qualitative analysis. The findings indicate that electronic medical records are legally acknowledged as valid evidence within the frameworks of health law and electronic information law. However, its admissibility is conditional, requiring compliance with authentication standards and guarantees of data integrity. In conclusion, while electronic medical records have legal recognition, their evidentiary validity is not automatic and depends on fulfilling specific technical and legal requirements to ensure legal certainty in medical disputes.